Milton and Homer : "Written to Aftertimes" - Machacek, Gregory (Book collections on Project MUSE., 2011)
"Explores the various ways in which Homer's epic poems influenced Milton in his own ambition to compose an enduring, canonical work of literature. Machacek's study of this major interpoetic relationship is methodologically responsive to the historicist critical enterprise dominant within literary study for the past three decades"--Provided by publisher.